Silver Diamine Fluoride Use among Dental Students and Pediatric Dentists: An Observational Study - Juliana da Silveira Gaiotto; Letícia Santos Alves de Melo; Marcia Hiromi Tanaka; Rita de Cássia Loiola Cordeiro; Elaine Pereira da Silva Tagliaferro; Angela Cristina Cilense Zuanon (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the use of silver diamine fluoride (SDF) among undergraduate dental students and graduate students/specialists in pediatric dentistry in Brazil. Material and Methods: The data were collected with online questionnaires sent to the participants (n=404) by e-mail and were analyzed by logistic regression models (α=0.05). Results: A total of 26.2% were unfamiliar with SDF. The product effectiveness (84.8%) was the main reason reported by respondents who used SDF in pediatric dental care. Professionals who had graduated for 1-15 years (OR=4.83), those with more than 15 years since graduation (OR=21.58), postgraduate students, graduates and professors (OR=10.01), or professionals who work in a dental office (OR=7.73) were more likely to have used the SDF. Most participants (67.8%) reported that they would use SDF even considering the unfavorable aesthetic result, especially those who would consider its use in a pandemic situation (OR=26.90), who know the SDF (OR=3.39), professionals who had graduated for 1-15 years (OR=2.40) or those with more than 15 years of graduation (OR=2.93). Conclusion: Most participants who know and use SDF are professionals who have graduated for longer and have more contact with the academic environment. Its use has become more considered by participants within a pandemic context.